Regular pulse checks for patients with non-cardioembolic stroke in rehabilitation hospitals to improve recognition and detection of atrial fibrillation (the ESCORT study): protocol for a prospective multicenter observational study - Katano, Takehiro; Suda, Satoshi; Ohta, Tomohiro; Miyagami, Mitsusuke; Kodaira, Yuzo; Konaka, Chimori; Nagashima, Masakazu; Kimura, Kazumi (Frontiers in Neurology, 2023)
Background: Cryptogenic stroke (CS) are heterogeneous in origin; however, most CS are embolic mechanism. Paroxysmal atrial fibrillation (AF) is suspected to be a major type of CS that leads to severe cerebral infarction without anticoagulant use. Therefore, the identification of AF is vital in patients with CS. However, patients are often unaware of AF because they have no symptoms, and AF may not be detected on an electrocardiogram (ECG) or Holter ECG on admission. After patients with stroke are treated in the acute phase, they are promptly transferred to a rehabilitation hospital for functional recovery. Once the patient is transferred to a hospital, a few attempts are made to detect AF. In addition, rehabilitation therapists are considered to have insufficient awareness of the possibility of undiagnosed AF.Objective: This study aimed to increase the understanding of the importance of AF detection in patients with ischemic stroke among therapists in rehabilitation hospitals and to investigate whether regular pulse screening can aid in the detection of AF. If AF was detected, we determined the rate and timing of AF detection and identified the patient characteristics.Methods: This multicenter prospective observational study aimed to detect AF in patients with noncardiac stroke at rehabilitation hospitals. Therapists performed pulse checks before, during, and after rehabilitation. If arrhythmia or tachycardia was detected, an ECG was performed, and the physician checked for AF. If the patient complained of chest symptoms, electrocardiography (ECG) was performed to check for AF. We investigated the characteristics, laboratory data, cognitive status, complications, such as stroke recurrence, and functional outcomes of patients with AF.The study is in the enrollment phase. Recruitment began in September 2022 and will end in August 2023. Patients have provided written informed consent. The main results have been submitted for publication in your journal.The findings of this study will help identify patients with AF in rehabilitation hospitals and improve awareness among therapists.